2014
DOI: 10.1182/blood.v124.21.664.664
|View full text |Cite
|
Sign up to set email alerts
|

Matching of MHC Class I Chain-Related Genes a and B Is Associated with Reduced Incidence of Severe Acute Graft-Versus-Host Disease after Unrelated Hematopoietic Stem Cell Transplantation

Abstract: Background: Graft-versus-host disease (GVHD) is a major cause of mortality after unrelated hematopoietic stem cell transplantations (HSCT). Despite the development of modern immunosuppressive strategies, a nearly perfectly controlled compatibility of the classical HLA genes (HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1) and availability of numerous so-called minor histocompatibility antigens (e.g. HY or HA-1), its incidence remains largely unexplained to date. MIC genes (MHC class I chain-related) - a distinct linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A comprehensive sequencing study of the MHC complex indicated that the sequence of MICA is more diverse than the sequence of HLA-DQB1 or HLA-DPB1, but the number of named MICA alleles is much lower (6,10). And even though MICA/B do not present antigenic peptides like the classical HLA class I genes, matching of MICA/B between patient and donor has been reported to improve outcome and reduce acute and chronic graft-vs.-host disease in hematopoietic stem cell transplantation, especially in partially matched scenarios (30,31,40). Translation of these findings into clinical practice is, amongst others, hampered by the lack of MICA/B genotyping data.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive sequencing study of the MHC complex indicated that the sequence of MICA is more diverse than the sequence of HLA-DQB1 or HLA-DPB1, but the number of named MICA alleles is much lower (6,10). And even though MICA/B do not present antigenic peptides like the classical HLA class I genes, matching of MICA/B between patient and donor has been reported to improve outcome and reduce acute and chronic graft-vs.-host disease in hematopoietic stem cell transplantation, especially in partially matched scenarios (30,31,40). Translation of these findings into clinical practice is, amongst others, hampered by the lack of MICA/B genotyping data.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of MICA allele disease associations are hampered by the strong linkage disequilibrium of MICA and HLA-B (17). In transplantation, increasing evidence supports independent positive effects of MICA matching on outcome (18)(19)(20)(21). In contrast, an independent role of MICA genotypes in addition to the well-established marker HLA-B*27 in ankylosing spondylitis (AS) remains questionable (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%